Desain dan Realisasi Antena Mikrostrip Patch Rectangular Array dengan Slit pada Frekuensi 2620-2690 MHz untuk Aplikasi LTE - Hanny Madiawati; Asep Barnas Simanjuntak (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2020)
LTE (Long Term Evolution) is a fourth generation wireless communication technology that is currently used by many people. To support the implementation of LTE, we need a reliable antenna and wide bandwidth. In recent years, the demand for compact antennas, low profile and broadband antennas has increased significantly. One type of antennas used is a microstrip antenna. Microstrip antennas can be made smaller by using miniaturization techniques, such as modifying antenna geometry using slots. Microstrip antenna with slots has potential to have a wide bandwidth and antenna array technique to increase gain which support the needs of LTE. Therefore,the aim ofthis research is the design and realization of 4 patch microstrip array antennas with slots for LTE application This antenna is obtained to work on the frequency band 2608 – 2701 MHz, bandwidth 93 MHz at 10 dB return loss and gain of 7,24 dB. This antenna obtained an increase in gain of 4,826 dB from single element and the antenna reduction of 0,12%.